Pengembangan Instrumen Tes Diagnostik Pilihan Ganda Tiga Tingkat untuk Mengidentifikasi Pemahaman Konsep Siswa MAN Blora pada Materi Gelombang Bunyi (UPEJ Unnes Physics Education Journal, 2021)
Three-Tier Diagnostic Tests is one of instrument to diagnosis. First tier consist of four multiple choice questions to identify students conceptual understanding, second tier consist of selection reason to identify students mindset, and third tier consist of convidience level who customized with CRI. Purpose of the research is develop three-tier diagnostic tests to identify of students conceptual understanding in sound wave. Procedural of the research use four-D models. Four-D models consist of Define, Design, Develop, and Disseminate. However, this research only restricted to develop. The result of the instruments that was developed consist of grille of three tier diagnostic test, instructions to answer the question, instrument of three tier diagnostic test, scoring guidelines, and guidelines of result interpretation. Reliability of the question is 0,61 and reliability of the reason is 0,67 so the instrument is reliable. Result from identify of students conceptual understanding is 35,62% students understand; 11,09% students not understand, and 53,28% students misconception.